Coastal Vulnerability Index Of Segeri, Pangkajene And Islands Regency - Paharuddin, Paharuddin; Irawan Alham; Muhammad Nadir; Syamsul Hadi (International Journal of Technology and Education Research, 2023)
The coastal area of Segeri sub-district, Pangkajene and Kepulauan Regency is a zone that is prone to natural phenomena of sea level rise. The impact received due to this phenomenon is something that needs to be studied to identify the level of coastal vulnerability and project changes in coastal vulnerability in the future. This study aims to calculate the coastal vulnerability index and project changes in vulnerability in the future due to changes in factors that affect coastal vulnerability.This research was conducted in August – December 2022 in Segeri District, namely in, Bone, Bawasalo and Bonto Matene Villages. The methods or approaches used in analyzing the data are: 1) analysis of coastal ecosystems and resources, 2) analysis of the physical and social characteristics of the community, 3) analysis of the vulnerability of the coastal environment. The Vulnerability Scoping Diagram (VSD) models places exposure, sensitivity and adaptive capacity as dimensions of vulnerability. The components of the exposure dimension consist of coastal dynamics, natural disturbances and population. The components of the sensitivity dimension are the characteristics of the coast, land use, and population settlements. The dimensions of adaptability include coastal habitats and marine conservation areas. Based on the scores of each parameter on the three dimensions, the coastal vulnerability index (IKP) in the three locations is in the range of IKP values ​​of 7.96 - 9.59 which is included in the category of moderate vulnerability. Factors that are very influential on the IKP are the dimensions of sensitivity including: erosion, waves and tides caused by oceanographic factors so that if adaptation and mitigation efforts are not carried out, it is likely that in the next 5-10 years, the level of vulnerability can become high and even very high. Adaptation efforts that can be done are strengthening the coastal border area, planting and expanding mangrove trees in the coastal area of ​​Segeri.